The Norton anthology of American literature : Volume E,. Literature since 1945 - Levine,Robert S (New York: W.W. Norton & Company, 2017)
This 9th edition of 'The Norton Anthology of American Literature' presents complete major works, balancing classic and newly emergent works
Keywords: American Literature -- Literary Collections